Local Fictionality within Global Nonfiction: Roz Chast's Can't We Talk about Something More Pleasant? (ENTHYMEMA, 2016)
This essay deploys a rhetorical approach to fictionality (defined as intentionally signaled communication in narrative) in order to analyze Roz Chast’s various uses of local fictionality within her graphic memoir about her parents’ end-of-life experiences. In so doing, it extends the contribution Chast’s memoir makes to the understanding of the many facets of end-of-life experiences for patients and their families by unpacking significant details of her exploration of her own experiences. The essay also contributes to conversations about the fiction/nonfiction distinction by (a) highlighting the presence of the narrative audience in fiction and its absence in local uses of fictionality in global nonfiction and (b) showing that the presence of local fictionality can enhance an author’s communication about actual events. Finally, the essay offers a preliminary and partial taxonomy of fictionality within the genre of graphic narrative.
Keywords: Fictionality; fiction/non-fiction; rhetoric; audience; graphic narrative; Roz Chast